Credibility, Accuracy, and Comprehensiveness of Readily Available Internet-Based Information on Treatment and Management of Peripheral Artery Disease and Intermittent Claudication: Review - Shelley Alexander; Chris Seenan (JMIR Publications, 2022)
BackgroundPeripheral artery disease (PAD) affects millions of people worldwide, and a core component of management of the condition is self-management. The internet is an important source of health information for many people. However, the content of websites regarding treatment recommendations for PAD has not been fully evaluated. ObjectiveThis study aimed to assess the credibility, accuracy, and comprehensiveness of websites found via a common search engine, by comparing the content to current guidelines for treatment and management of PAD and intermittent claudication (IC). MethodsA review of websites from hospitals, universities, governments, consumer organizations, and professional associations in the United States and the United Kingdom was conducted. Website recommendations for the treatment of PAD and IC were coded in accordance with the guidelines of the National Institute for Health and Care Excellence (NICE) and the American Heart Association (AHA). Primary outcomes were website credibility (4-item Journal of the American Medical Association benchmark), website accuracy (in terms of the percentage of accurate recommendations), and comprehensiveness of website recommendations (in terms of the percentage of guideline recommendations that were appropriately covered). Secondary outcomes were readability (Flesch-Kincaid grade level) and website quality (Health On the Net Foundation's code of conduct). ResultsAfter screening, 62 websites were included in this analysis. Only 45% (28/62) of websites met the credibility requirement by stating they were updated after the NICE guidelines were published. Declaration of authorship and funding and the presence of reference lists were less commonly reported. Regarding accuracy, 81% (556/685) of website recommendations were deemed accurate on following NICE's and the AHA's recommendations. Comprehensiveness was low, with an average of 40% (25/62) of guideline treatment recommendations being appropriately covered by websites. In most cases, readability scores revealed that the websites were too complex for web-based consumer health information. ConclusionsWeb-based information from reputable sources about the treatment and management of PAD and IC are generally accurate but have low comprehensiveness, credibility, and readability.